Laterality and risk factors for ulnar neuropathy at the elbow. Issue 1 (23rd October 2019) - Ashworth, Nigel L.; Huang, Christopher; Chan, K. Ming
Abstract: Background: Ulnar neuropathy at the elbow (UNE) is the second commonest entrapment neuropathy after carpal tunnel syndrome (CTS) and yet the laterality is not well delineated. Our aim was to establish the laterality of UNE in a large cohort of patients. Methods: All new patients with clinical and electrodiagnostic (EDX) confirmed UNE over a 13‐year period were included. We used multivariate analysis to examine potential predictors of laterality, and unilateral vs bilateral UNE. Results: Of 880 cases, 61% were left‐sided and 39% right‐sided. These proportions did not change regardless of the handedness of the patient. Patients with bilateral UNE were much more likely to be older male and have a variety of comorbidities. Conclusions: UNE appears to be present on the left 50% more often than on the right, regardless of the patient's handedness.